Analisis Key Performance Indicator Pada Pelayanan Customer Service di Stasiun KIaracondong - Nurhalimah, Dela; Kustiwa, Atep (JURNAL MANAJEMEN DAN BISNIS, 2024)
This study aims to find out what points are being studied to meet the Key Performance Indicators at Kiaracondong Station. How do Customer Service officers at Kiaracondong Station comply with applicable customer service procedures. As well as analyzing the role of Customer Service at Kiaracondong Station in fulfilling Key Performance Indicator (KPI) points. This scientific research obtained data using descriptive qualitative methods. Data collection techniques are carried out in natural settings, primary data sources, and data collection techniques are more in participan observation, in depth interviews, and documentation. The data obtained and presented came from sources at the research location and informants consisting of: Informant 1 SPV Customer Care, Informant 2 and 3 Customer Service Officers. The results of this scientific research show that Customer Service services at Kiaracondong Station are in accordance with KPI points which include Service SOPs, 7S Culture, Grooming, and AKHLAK Core Values. Officers carry out SOPs consistently and become the face of the company in building customer satisfaction. They also act as a liaison between the system and customers, and show high loyalty despite facing personnel limitations. Routine evaluation and application of AKHLAK values strengthens the work culture and supports the achievement of KPIs strategically.